Efektivitas Terapi Plasma Konvalesen pada Pasien Covid-19 Derajat Berat dan Kritis dari Laporan Kasus dan Seri Kasus: Tinjauan Sistematis - sity kunarisasi (State Islamic University of Sunan Ampel, 2023)
Severe acute respiratory syndrome (SARS-CoV-2) causes the 2019 Coronavirus Disease pandemic. Convalescent plasma is the first choice in the current situation because it has been used successfully in other coronavirus outbreaks. Convalescent plasma administration has an immunomodulatory effect on the lungs through the induction of anti-inflammatory cytokines and antibodies that inhibit the complement cascade (C3a, C5a) and the antiviral effect of NAbs. IgG and IgM are the main isotypes, and the humoral immune response is primarily the spike protein (S). Its anti-inflammatory effect controls an overactive immune system (cytokine storm, Th1/Th17 ratio, complement activation and regulation of hypercoagulable states) and synergistically with standard therapy leads to the development of primary clinical outcomes. The use of convalescent plasma has an impact on reducing the morbidity of patients with severe or critical COVID-19.